Mixed convection flow over a stretching porous wedge with Newtonian heating in the presence of heat generation or absorption - Ashraf, M. (American Institute of Physics Inc., 2016)
Time independent mixed convective boundary layer flow of a viscous fluid over a porous stretching wedge is investigated analytically. The porous wedge is subjected to Newtonian heating in the existence of heat generation /absorption. Employing non-dimensional transformations the governing PDE's converted to nonlinear ODE's which are further solved by using homotopy analysis method. The convergence of the solution is properly checked and the effects of various involved parameters on velocity and temperature distributions are illustrated through graphs. The reliability and effectiveness of HAM have been verified by comparing the present analytical results with existing numerical results for skin-friction coefficient. The results are found to be in good agreement. Â© 2016 Author(s).